2007
DOI: 10.1038/sj.bjc.6603966
|View full text |Cite
|
Sign up to set email alerts
|

Marrow angiogenesis-associated factors as prognostic biomarkers in patients with acute myelogenous leukaemia

Abstract: Bone marrow (BM) neoangiogenesis plays an important role in acute myelogenous leukaemia (AML), and depends on the interplay of members of the vascular endothelial growth factor (VEGF) and angiopoietin (Ang) families. We determined the marrow levels of seven molecules associated with angiogenesis in 52 AML patients before chemotherapy and 20 healthy controls: VEGF-A, VEGF/PlGF, VEGF-C, VEGF-D, Ang-1, Ang-2, and Tie-2. All the molecules were quantified using enzyme-linked immunosorbent assay (ELISA). Comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 33 publications
5
30
1
Order By: Relevance
“…The regulatory role of Ang-1 and Ang-2 in tumor angiogenesis remains controversial due to the conflicting roles of both angiopoietins in angiogenesis [11]. Ang-1 activates Tie2 more strongly than does Ang-2; thus, some of the effects of Ang-2 could result from the inhibition of Ang-1 signaling [1,12]. Ang-1-Tie2 signaling is thought to limit angiogenesis in mature vessels [1].…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory role of Ang-1 and Ang-2 in tumor angiogenesis remains controversial due to the conflicting roles of both angiopoietins in angiogenesis [11]. Ang-1 activates Tie2 more strongly than does Ang-2; thus, some of the effects of Ang-2 could result from the inhibition of Ang-1 signaling [1,12]. Ang-1-Tie2 signaling is thought to limit angiogenesis in mature vessels [1].…”
Section: Introductionmentioning
confidence: 99%
“…The threeyear survival rate for AML patients with high levels of Ang-2 was only 14.7% compared to 64.7% for those with low Ang-2 levels. Furthermore, Lee et al [20] reported that AML patients with lower Ang-2 and Tie-2 levels displayed a survival advantage.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF can influence and regulate the malignant behavior of leukemic cells via paracrine and autocrine pathways [12], and high levels of plasma VEGF in AML patients indicate a poor prognosis [13]. A high VEGF level in childhood AML is also an independent factor indicating poor prognosis [14], suggesting that VEGF inhibition can have potential therapeutic effects on AML.…”
Section: Discussionmentioning
confidence: 99%